2020
DOI: 10.1002/hyp.13722
|View full text |Cite
|
Sign up to set email alerts
|

A 2D hydrodynamic model for shallow water flows with significant infiltration losses

Abstract: Infiltration losses may be significant and warrant proper incorporation into mathematical models for river floods in arid and semi-arid areas, rainfall-induced surface runoffs in watersheds and swashes on beaches. Here, a depth-averaged twodimensional hydrodynamic model is presented for such processes based on the cellcentred finite volume method on unstructured meshes, with the full Green-Ampt equation evaluating the infiltration rate. A local time stepping strategy is employed along with thread parallelizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…Conversely, Ribolzi et al [57] showed in their study about field experiments on steep slopes with a texture class of clay loam, that microterraces tend to form on a slope of 75 %, and are significantly more pervious than the ripple-like roughness that occurred on a gentler slope of 30 %. Furthermore, their observations confirmed the hypothesis that higher effective rainfall intensity was responsible for the formation of less permeable erosion crusts on the 30 % slope the last more than 100 years, and in many test cases it was proven that this model is generally able to appropriately represent infiltration processes [17,38,48,73]. The fractured-order Green-Ampt (FOGA) model as introduced e.g.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Conversely, Ribolzi et al [57] showed in their study about field experiments on steep slopes with a texture class of clay loam, that microterraces tend to form on a slope of 75 %, and are significantly more pervious than the ripple-like roughness that occurred on a gentler slope of 30 %. Furthermore, their observations confirmed the hypothesis that higher effective rainfall intensity was responsible for the formation of less permeable erosion crusts on the 30 % slope the last more than 100 years, and in many test cases it was proven that this model is generally able to appropriately represent infiltration processes [17,38,48,73]. The fractured-order Green-Ampt (FOGA) model as introduced e.g.…”
Section: Introductionmentioning
confidence: 66%
“…Hydrodynamic models are more and more used to simulate not only the flow and flooding areas of surface waters but also rainfall-induced overland flow in small catchments [6,34,43,63,75], the propagation of flash floods [1,5,26,69], and flood inundation in urban areas [9,32,59,80]. Due to the enhanced accuracy and resolution of topographic data, the interest in using 2D hydrodynamic models is continuously increasing, and since different techniques of high-performance computing are developed to accelerate numerical computations, the powerful potential of shallow water models can be realized more and more and be used also in practical applications [33,48].…”
Section: Introductionmentioning
confidence: 99%
“…Then, according to a Shields curve for cohesive silt (Miedema, 2013), the Shields parameter was determined. Finally, the critical shear stress was calculated from (Ni et al, 2020; Parker et al, 2003): τc=ρwitalicRgDτc* where τc* is the critical Shields number. Equations and were then applied following Antoniazza et al (2019): qbx=τx2τx2+τy2[]k=18qbk+ρ()1pVijt qby=τy2τx2+τy2[]k=18qbk+ρ()1pVijt where t is the duration of competent flow; k is the index of each of the eight surrounding cells that could deliver sediment to cell ij ; and Δ V ij is the net volume change measured by DEM differencing.…”
Section: Methodsmentioning
confidence: 99%
“…In investigations of Caviedes-Voullième et al [3], the SCS-CN method was found to be inadequate to be coupled with a distributed model for runoff computations, and as the Richards equation is very complex and the solution needs a lot of computational effort as well as many measured data [37,38], simplified equations are often used in rainfall-runoff models, where the Green-Ampt model is one of the most popular ones [4,16,39,40]. Developed by Green and Ampt already in 1911 [41], many different applications, modifications, and extensions have been carried out in the last more than 100 years, and in many test cases, it was proven that this model is generally able to appropriately represent infiltration processes [16,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%